PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA DENGAN PENERAPAN PENDEKATAN INKUIRI TERBIMBING DI KELAS XII IPA3 SMA NEGERI 4 KOTA BENGKULU - Deny Asiah (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
This research aims to increase activity and mathematics student learning outcomes through inquiry learning approach. Places that are used in this study were SMA Negeri 4 Kota Bengkulu with research subjects are class XII IPA3 student, amounting to 32 students. This type of research is a descriptive qualitative research methods class action, which is implemented in two cycles, each cycle consisting of three meetings. The process of implementation of research include: the planning, implementation actions, monitoring and reflection. The results obtained in this study show that: 1) Average activity in cycle I (48.73%) increased by 14.92% in cycle II (63.65%), 2) Improved student learning outcomes of the cycle I to the second cycle of 28.57% from 57.14% to 85.71% cycle I to cycle II on the subject of mathematic. Based on these results, the suggestions can be submitted are: to improve the quality of teachers should be teaching mathematic in the inquiry learning approach. For researchers, in order to do further research on the effectiveness of learning by using the inquiry approach related to learning outcomes and learning processes, and are expected to contribute to the awakening of science and technology, especially learning mathematics.